Optimizing Students' Critical Thinking Skills through PhET Simulation-Based Problem-Based Learning Model - Putri Pratiwi, Dhea; Acesta, Arrofa; Nugraha, Febby Fajar (Journal Of Educational Experts (JEE), 2026)
This research is motivated by the low level of students' critical thinking skills in Natural Science learning, which stems from students' lack of activity and the implementation of teaching models that do not emphasize critical thinking skills. This study aims to determine the difference in critical thinking skills between the experimental class, which utilized the PhET simulation-aided Problem-Based Learning (PBL) model, and the control class, which utilized the Cooperative Learning model. Furthermore, it aims to analyze the difference in the improvement of critical thinking skills between the two groups. This research adopts a quantitative approach with a quasi-experimental research type and a non-equivalent control group design. The subjects of this study were sixth-grade students at SD Negeri 1 Cimaranten. Data were collected using a test instrument consisting of 6 essay questions. Based on the results, it can be concluded that: (1) there is a significant difference in critical thinking skills between the experimental class using the PhET simulation-aided PBL model and the control class using the Cooperative Learning model; (2) there is a significant difference in the improvement of critical thinking skills between the experimental class and the control class.